Multiple sclerosis therapies in pediatric patients with refractory multiple sclerosis - Yeh, E Ann; Waubant, Emmanuelle; Krupp, Lauren B; Ness, Jayne; Chitnis, Tanuja; Kuntz, Nancy; Ramanathan, Murali; Belman, Anita; Chabas, Dorothee; Gorman, Mark P; Rodriguez, Moses; Rinker, 2nd, John Robert; et al. (Archives of neurology (Chicago), 2011)
Currently available disease-modifying therapies (DMTs) are known to be only partially effective in adults with multiple sclerosis (MS). Little is known about pediatric patients with MS who experience refractory disease while receiving first-line DMTs. To assess the occurrence and management of refractory disease in a group of pediatric patients with MS treated with first-line DMTs approved for adult patients within a network of pediatric MS centers in the United States. A multicenter, retrospective, longitudinal, open-label study design involving record review of 258 patients with pediatric-onset MS (68.6% female; mean [SD] age at disease onset, 13.2 [3.5] years; range of age at onset, 2.0-17.9 years) who were seen at 6 pediatric MS centers in the United States. We evaluated medication changes owing to refractory disease in cases of pediatric-onset MS. Disease stability as represented by lack of medication change for breakthrough disease. Records of 258 children with a confirmed diagnosis of MS and exposure to DMTs were reviewed. Interferon beta (prescribed to 200 of 258 children [77.5%]) and glatiramer acetate (prescribed to 53 of 258 children [20.5%]) were the 2 most frequently used first-line DMTs. Overall, 144 children (55.8%) continued receiving 1 therapy, while 65 (25.2%), 29 (11.2%), and 20 (7.8%) received 2, 3, or 4 or more sequential therapies, respectively, during a mean (SD) observation period of 3.9 (2.8) years. Second-line DMT use was restricted to interferon beta and glatiramer acetate in 203 children (78.7%), whereas other treatments such as broad-spectrum chemotherapies (cyclophosphamide, mitoxantrone hydrochloride), natalizumab, corticosteroids (monthly), and daclizumab were used at some point during the observation period for disease management in 55 children (21.3%). Hispanic children were more likely to experience breakthrough disease while receiving first-line DMTs than non-Hispanic children. Although switching between first-line DMTs may be effective in pediatric patients with disease that is refractory to initial treatment, a subset of patients may require second-line therapeutic interventions.